Immobilization and microencapsulation of Lactobacillus caseii and Lactobacillus plantarum using zeolite base and evaluating their viability in gastroesophageal-intestine simulated condition - Azad Mohammad Hassanzadeh; Sowti Khiabani Mahmoud; Mahshidsadat Sadrnia; Baharak Divband; Omid Rahmanpour; Vahid Jabbari; Pourya Gholizadeh; Samadi Kafil Hossein
ABSTRACT Aims: In order to improve survival in gastrointestinal conditions, probiotic bacteria, i.e. we developed a new encapsulation method of probiotics based on zeolite and by calcium-alginate zeolite-starch as an effective method for safer delivery of probiotics. Material and Methods: Lactobacillus casei (ATCC 39392) and Lactobacillus plantarum (ATCC 29521) were used as probiotics. After microorganism's immobilization on zeolite base, encapsulation was done by calcium-alginate zeolite-starch with the extrusion method. Afterwards, they were incubated in the simulated gastric and intestinal condition. Viability of these bacteria was calculated on the basis of time required to reduce the logarithmic base in the microbial population. SEM techniques were used to study the appearance of the capsules. Results: after incubation for 120 min under simulated gastric condition and 180 min in intestinal juice conditions (pH=8.2), the count of alive L. casei and L. plantarum cells were 6.3 log cfu/ml and 7.3 log cfu/ml. However, for controlling the cells, this value was zero and 2.1 log cfu/ml respectively. Conclusion: According to the results, we had an increase of the survival rate of L. casei and L. plantarum in gastroesophageal-intestine simulated condition. These results indicated good efficacy and high performance of zeolite for immobilization and microencapsulation of probiotics.